Prediction of Turbulence Statistics in a Model Dump Combustor Using Artificial Neural Networks - AlSharif, Amin Moh'd (2011)
A Master of Science Thesis in Mechanical Engineering submitted by Amin Moh'd AlSharif entitled, "Prediction of Turbulence Statistics in a Model Dump Combustor Using Artificial Neural Networks," submitted in May 2011. Available are both soft and hard copies of the thesis.